IoT Based Vehicle Overload Detection and Preventing Accident (International Research Journal on Advanced Electronics and Computer Technology (IRJAECT), 2025)
This project presents an Arduino-based vehicle overload detection system aimed at preventing accidents through the use of Internet of Things (IOT) technology. The system addresses the critical safety issue of vehicle overloading, which is a significant contributor to road accidents. The vehicle is equipped with load sensors connected to an Arduino microcontroller that continuously monitors its weight. If the vehicle exceeds a specified weight limit, it will not start, thereby preventing potential accidents caused by overloading. In cases where starting the vehicle is necessary, the driver must press a designated secret key, allowing for a manual over ride. Upon activation of this secret key, the system automatically sends an SMS containing the vehicle's location to the nearest police station. This timely notification enables law enforcement to take appropriate action against overloaded vehicles, enhancing public safety. By integrating load detection with IOT communication, this project provides a practical and effective solution for managing vehicle overload. The implementation of this system not only promotes compliance with safety regulations but also contributes to reducing road accidents, ultimately fostering safer driving conditions.